Analisis Harga Pokok Produksi Menggunakan Metode Full Costing Diusaha Keripik Kanala Desa Totokaton - Rivaldy, Muhamad; Dupri, Muhammad Demsi (Jurnal Manajemen DIVERSIFIKASI, 2023)
Determination of the cost of production is very important considering the benefits ofinformation on the cost of production are to determine the selling price of products, tomonitor the realization of production costs, to calculate periodic income and to determine thecost of inventories of finished products and products in process which are presented in thebalance sheet. In determining the cost of production, two methods can be used, namely thefull costing method and the variable costing method. In the full costing method, all costs arecalculated, both fixed and variable, because one way to control costs is to calculate the costof production to determine the selling price of the product itself. This study aims to determinethe calculation of the cost of production using the Full Costing method. The type of researchcarried out by the researcher is field research or field research, where field research is aresearch conducted at the research location with a qualitative descriptive nature. Datacollection techniques researchers used interviews and documentation. The interviewtechnique in this study used a guided free interview. The source of the data was taken by theowner of the Kanala Chips UMKM and records of the production costs of Kanala ChipsUMKM.